Nilai Islam dalam Lambang Siger Lampung - Badaruddin, Badaruddin Badaruddin (BINA' AL-UMMAH, 2017)
Abstract This research is literature research, where the researcher tries to explore the literature sources related to Lampung culture symbol that is Siger, and the history books of Lampung cultural development both from geographical and demographic aspect. Likewise the history of the development of Islam in Lampung. Interaction of cultural values of Lampung with religious values. In sociology and anthropology studies, symbols have deep meaning, every society, usually have symbols that are typically believed and understood for members of the group. These symbols contain meaning and values, These meanings and values are sometimes considered sacred and approach religious teachings. For societies with religious characteristics, usually the values contained in societal symbols are derived from the values of the principles of religious teachings that are adapted to their traditions, hence this issue becomes an attraction for researchers to conduct research in this field, especially if associated with Islamic da'wah activities. Lampung consists of two groups, the people of Pepadun (Outback) and Coastal. Both communities have different settlements. Both also have the customs and properties are slightly different, so interesting to learn and see the difference further. From the results of this study it can be concluded that religious values have a very big influence on the cultural values of Lampung symbolized in the form of Siger. Siger Lampung symbol is a blend of cultural and religious values, therefore both of these values play a major role in creating harmony of life of Lampung society. Or in other words the people of Lampung is a society that has high regigiusitas nature.Kata Kunci: Nilai –nilai Islam, Lambang Siger Lampung